2023
DOI: 10.1038/s41598-023-31906-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of machine learning models’ accuracy in predicting lower-limb joints’ kinematics, kinetics, and muscle forces from wearable sensors

Abstract: A combination of wearable sensors’ data and Machine Learning (ML) techniques has been used in many studies to predict specific joint angles and moments. The aim of this study was to compare the performance of four different non-linear regression ML models to estimate lower-limb joints’ kinematics, kinetics, and muscle forces using Inertial Measurement Units (IMUs) and electromyographys’ (EMGs) data. Seventeen healthy volunteers (9F, 28 ± 5 years) were asked to walk over-ground for a minimum of 16 trials. For e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
1
21
2
Order By: Relevance
“…2, Step 5). The hyperparameters for both RF and CNN models were chosen based on previously optimized models (Moghadam et al, 2023a). We employed an RF model comprising 500 trees, each with a maximum depth of 25.…”
Section: Non-linear Regression ML Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, Step 5). The hyperparameters for both RF and CNN models were chosen based on previously optimized models (Moghadam et al, 2023a). We employed an RF model comprising 500 trees, each with a maximum depth of 25.…”
Section: Non-linear Regression ML Modelsmentioning
confidence: 99%
“…However, there is a limited body of literature exploring alternative data-driven models that may demand smaller datasets while achieving comparable results to ANNs. Building on this context, in a prior study, we demonstrated that Random Forest (RF) models can yield results comparable to more intricate machine learning models such as Convolutional Neural Networks (CNNs) for 3D Gait Analysis (3DGA) in adults (Moghadam et al, 2023a). Given the greater heterogeneity in children's gait, it will be interesting to explore whether RF or CNNs can be applied to a paediatric population with similar performances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have addressed joint behavior under various conditions including loading, lubrication, and mechanics of the cartilage and surrounding tissues. 61,62 However, they rely on accurate input data and assumptions, which may introduce uncertainties and simplifications. 63,64 For example, while there are numerous studies addressing inorganic or carbon-based NC transport, polymeric NC models are more difficult to build due to more complex structural properties and more sensitive physicochemical parameters.…”
Section: Vessel-on-a-chip Models: Understanding Nanomedicine Transportmentioning
confidence: 99%
“…Based on mathematical equations and computer-driven analysis, models such as finite element analysis (FEA) or multibody dynamic simulations can provide valuable insights into tissue mechanics, function, and NC toxicity. , They offer a cost-effective approach to study joint biomechanics and allow rapid exploration of different scenarios and parameter variations. Several studies have addressed joint behavior under various conditions including loading, lubrication, and mechanics of the cartilage and surrounding tissues. , However, they rely on accurate input data and assumptions, which may introduce uncertainties and simplifications. , For example, while there are numerous studies addressing inorganic or carbon-based NC transport, polymeric NC models are more difficult to build due to more complex structural properties and more sensitive physicochemical parameters . The complexity of the NC-cell interactions also poses an additional challenge where a vast majority of descriptors must be included to replicate the dynamic nature of cellular membranes and the glycocalyx. , Such drawbacks may make computational models generalized or biased, missing out on biologically relevant complexities of in vivo joint physiology.…”
Section: Advanced Models To Explore Personalized Nanomedicinesmentioning
confidence: 99%